2001
DOI: 10.1002/path.918
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of oncogenesis in colon versus rectal cancer

Abstract: Observations support the theory that development of left- and right-sided colorectal cancers may involve different mechanisms. This study investigated different genes involved in oncogenesis of colon and rectal cancers and analysed their prognostic value. The study group comprised 35 colon and 42 rectal cancers. Rectal cancer patients had been treated with standardized surgery performed by an experienced rectal cancer surgeon. Mutation analysis was performed for p53 in eight colon cancers and for APC and p53 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
117
6
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(145 citation statements)
references
References 30 publications
14
117
6
7
Order By: Relevance
“…Furthermore, we found a difference in the relation between p53 mutations and stromal MSI (stromal MSI þ /p53 mutation, 3/11 (27%) in the left-side; 3/4 (75%) in the right-side, P ¼ 0.0952). These results support the conclusion of Kapiteijn et al (2001) and suggest a relation of p53 mutation to stromal MSI þ .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, we found a difference in the relation between p53 mutations and stromal MSI (stromal MSI þ /p53 mutation, 3/11 (27%) in the left-side; 3/4 (75%) in the right-side, P ¼ 0.0952). These results support the conclusion of Kapiteijn et al (2001) and suggest a relation of p53 mutation to stromal MSI þ .…”
Section: Discussionsupporting
confidence: 87%
“…Recently, Kapiteijn et al (2001) reported that p53 gene mutation corresponds more often to p53 overexpression in left-than in right-sided tumours, suggesting that mechanisms of oncogenesis may differ between the two cases. This is in line with our results for a greater prevalence of p53 overexpression with p53 gene mutations in left-sided tumours (9/11, 81%), than in those found on the right side (1/4, 25%) (P ¼ 0.0390, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A second issue that makes the findings of previous work hard to interpret specifically for colon cancer is the lack of differentiation that all but 2 14,15 of the discussed articles make between colon and rectal disease -an issue shared with many publications on the matter. [19][20][21] Malignancies of the colon and rectum have been shown to be quite different in tumor biology 22 and subsequent prognosis 23 and arguments to split both are a recurring issue in outcome studies. 24 Our work is therefore the first to review a large cohort of colon cancer-specific patients in a single center.…”
Section: Commentsmentioning
confidence: 99%
“…For these reasons, it is important to rid proteins of their sugar adducts rather than replace them with newly synthesized macromolecules. Different studies have demonstrated a better clinical outcome for the patients with proximal colorectal cancer with respect to distal colorectal cancer [2,11]. Colonic cells of proximal colon appear to have more efficient mechanisms to protect their proteins against the glycating effects of high glucose or fructose compared to distal colon cells.…”
Section: Discussionmentioning
confidence: 99%